2017
DOI: 10.20959/wjpr20178-9015
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Dairy Wastewater by Moringa Oleifera Seeds

Abstract: Therefore, application of this low cost Moringa oleifera seeds is recommended for ecofriendly, nontoxic, simplified waste water treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Significant removal of COD achieved by okra coagulant compared to alum in dairy wastewater (Balamurugan & Shunmugapriya, 2019). Another study by Chonde & Raut, (2017) stated that M. oleifera seeds had similar coagulation properties to conventional coagulants such as alum which indicated that natural coagulants could be another approach to reducing the drawbacks of conventional coagulants towards the ecosystem. The COD removal efficiency of M.oleifera is high, which shows 75.6%, with minimal drawbacks to ecosystem compared to conventional coagulants (Fagundes-klen & Dotto, 2019).…”
Section: Meta-analysis On Chemical Oxygen Demandmentioning
confidence: 99%
“…Significant removal of COD achieved by okra coagulant compared to alum in dairy wastewater (Balamurugan & Shunmugapriya, 2019). Another study by Chonde & Raut, (2017) stated that M. oleifera seeds had similar coagulation properties to conventional coagulants such as alum which indicated that natural coagulants could be another approach to reducing the drawbacks of conventional coagulants towards the ecosystem. The COD removal efficiency of M.oleifera is high, which shows 75.6%, with minimal drawbacks to ecosystem compared to conventional coagulants (Fagundes-klen & Dotto, 2019).…”
Section: Meta-analysis On Chemical Oxygen Demandmentioning
confidence: 99%
“…M. oleifera is a medium size multipurpose tree found in northwest India and native to various parts of Asia, South America and Africa [3]. Pods of M. oleifera are non-hazardous and can be utilized as an economical and effective sorbent for the elimination of organics [4]. Application of alum and lime is a conventional coagulant used for water treatment worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this sustainable development, it is necessary to put into service the plant-based natural coagulant [3,8]. It is an eco-friendly and cheaper method for purification of industrial wastewater as compared to common coagulants like alum [2][3][4]9]. Table 2 shows the comparison between chemical (common) coagulant and natural coagulants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation